1999
DOI: 10.1111/j.1469-8749.1999.tb00523.x
|View full text |Cite
|
Sign up to set email alerts
|

Medical aspects of school‐aged children with Down syndrome

Abstract: Current and comprehensive information about the medical issues affecting children with Down syndrome (DS) is of value in counselling parents who are considering prenatal diagnosis and in planning services for people with DS as they age, especially given the continued improvements in their survival. Parents of school-aged children (mean age 11.37 years, 57.3% male, 42.7% female) with DS were identified by linking registers from the Disability Services Commission and the Birth Defects Registry. Less than half th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…We found that malformations, diseases of the respiratory system, and diseases of the nervous system or sensory organs were the main reasons for hospitalization among people with DS, in accordance with most studies [Turner et al, 1990; Hilton et al, 1999; Leonard et al, 1999; Frid et al, 2002; van Trotsenburg et al, 2006; So et al, 2007; Schieve et al, 2009; Thomas et al, 2011]. Our finding that persons with DS who had congenital heart defects were more likely to be hospitalized and to stay longer in the hospital than persons with DS who did not have cardiac malformations is also in agreement with previous reports [Hilton et al, 1999; Frid et al, 2002; So et al, 2007].…”
Section: Discussionsupporting
confidence: 89%
“…We found that malformations, diseases of the respiratory system, and diseases of the nervous system or sensory organs were the main reasons for hospitalization among people with DS, in accordance with most studies [Turner et al, 1990; Hilton et al, 1999; Leonard et al, 1999; Frid et al, 2002; van Trotsenburg et al, 2006; So et al, 2007; Schieve et al, 2009; Thomas et al, 2011]. Our finding that persons with DS who had congenital heart defects were more likely to be hospitalized and to stay longer in the hospital than persons with DS who did not have cardiac malformations is also in agreement with previous reports [Hilton et al, 1999; Frid et al, 2002; So et al, 2007].…”
Section: Discussionsupporting
confidence: 89%
“…Subjects in the cohort were ascertained from two sources: the population‐based Western Australian Birth Defects Registry (BDR) (Bower et al. 2000) and the Disability Services Commission (DSC), a multidisciplinary government body responsible for co‐ordinating the medical and therapy services for all people with an ID in Western Australia (Leonard et al. 1999).…”
Section: Methodsmentioning
confidence: 99%
“…While siblings of children with Down syndrome have been the subject of small studies, there have been no reports involving population‐based samples. Our research group has for some years been undertaking population‐based research both on Down syndrome (Leonard et al. 1999), and on Rett syndrome (Laurvick et al.…”
Section: Introductionmentioning
confidence: 99%
“…Only one study employed a sample frame (general practices in the Netherlands) broadly representative of people with intellectual disability (Straetmans, van Schrojenstein Lantman-de Valk, Schellevis, & Dinant, 2007). A further six studies employed a sample broadly representative of people with intellectual disability from a particular subpopulation: Down syndrome (Alexander et al, 2015;Yin, Boyd, Pacheco, Schonfeld, & Bove, 2012), children with Down syndrome (Leonard, Bower, Petterson, & Leonard, 1999;Thomas et al, 2011), children with severe generalized cerebral palsy (Veugelers et al, 2010), and adults with ASD (Jones et al, 2015).…”
Section: Risk Of Biasmentioning
confidence: 99%